Proceedings of the 2017 Federated Conference on Computer Science and Information Systems 2017
DOI: 10.15439/2017f397
|View full text |Cite
|
Sign up to set email alerts
|

Aspect-driven Context-aware Services

Abstract: Abstract-Nowadays enterprise software solutions must deal with ever-growing complexity and a multitude of business processes. The mainstream system design decomposes the system into small reusable services. While these services isolate certain system logic and address efficient elasticity towards growing user demands, there are multiple issues related to such a design, such as limitations to deal with restated information, information reuse or the ability to address cross-cutting concerns across multiple servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…If one manages to capture business rules in such a unified approach, it is possible to extract business rules and consider them for transformation or even the AOP process for UI fragment derivation. For instance, [80], [81] shows that it is easy to extract business rules from Drools and convert them to documentation or even enforce clientside validation already in the UI. This could be utilized for knowledge base exchange across smart interacting systems.…”
Section: Advanced Options In Ui Derivationmentioning
confidence: 99%
See 3 more Smart Citations
“…If one manages to capture business rules in such a unified approach, it is possible to extract business rules and consider them for transformation or even the AOP process for UI fragment derivation. For instance, [80], [81] shows that it is easy to extract business rules from Drools and convert them to documentation or even enforce clientside validation already in the UI. This could be utilized for knowledge base exchange across smart interacting systems.…”
Section: Advanced Options In Ui Derivationmentioning
confidence: 99%
“…For instance, in enterprises we can use DSL to describe processes [106] or rules [79]. It can be business rules [80] or security rules. Modern frameworks also make it possible to define specific processes using DSL and utilize modeling tools on top of the DSL [107].…”
Section: B Language Domain Specificitymentioning
confidence: 99%
See 2 more Smart Citations
“…usually deemphasized when analysing communication in large-scale industrial IoT deployments. In a paper [22], the authors identified REST as one of the leading standards for communication between microservices, without examining its impact on the overall system performance. Interesting, from the point of view of the conducted research, is an article available on the blog of the developers of the gRPC framework.…”
Section: Introductionmentioning
confidence: 99%